The Iran-Iraq War a military and strategic history - Murray, Williamson (Cambridge University Press, 2014)
The Iran-Iraq War is one of the largest, yet least documented conflicts in the history of the Middle East. Drawing from an extensive cache of captured Iraqi government records, this book is the first comprehensive military and strategic account of the war through the lens of the Iraqi regime and its senior military commanders. It explores the rationale and decision-making processes that drove the Iraqis as they grappled with challenges that, at times, threatened their existence. Beginning with the bizarre lack of planning by the Iraqis in their invasion of Iran, the authors reveal Saddam's desperate attempts to improve the competence of an officer corps that he had purged to safeguard its loyalty to his tyranny, and then to weather the storm of suicidal attacks by Iranian religious revolutionaries. This is a unique and important contribution to our understanding of the history of war and the contemporary Middle East
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Iran-Iraq War, 1980-1988; Golfkrieg -- 1980-1988